1997
DOI: 10.1073/pnas.94.13.6682
|View full text |Cite
|
Sign up to set email alerts
|

Pacifastin, a novel 155-kDa heterodimeric proteinase inhibitor containing a unique transferrin chain

Abstract: A 155-kDa proteinase inhibitor, pacifastin, from plasma of the freshwater crayfish, Pacifastacus leniusculus, was found to be composed of two covalently linked subunits. The two subunits are encoded by two different mRNAs, which were cloned and sequenced. The heavy chain of pacifastin (105 kDa) is related to transferrins, containing three transferrin lobes, two of which seem to be active for iron binding. The light chain of pacifastin (44 kDa) is the inhibitory subunit, and has nine cysteine-rich inhibitory do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 47 publications
1
88
0
Order By: Relevance
“…One should bear in mind that the activation of such serine protease cascades must be tightly controlled. Serine proteinase inhibitors are, henceforth, employed to regulate this activation process by preventing excessive activation that is often fatal to hosts (33,41,42). In Drosophila, the spn27A 1 , a mutant lacking spn27A, shows excessive melanization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One should bear in mind that the activation of such serine protease cascades must be tightly controlled. Serine proteinase inhibitors are, henceforth, employed to regulate this activation process by preventing excessive activation that is often fatal to hosts (33,41,42). In Drosophila, the spn27A 1 , a mutant lacking spn27A, shows excessive melanization.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of dsRNA-Oligonucleotide primers with T7 promoter sequences (italic) at the 5Ј-ends were synthesized to amplify a 692-bp and 550-bp region of the P. leniusculus proPO gene and pacifastin light chain, the inhibitory subunit, gene (33), respectively, from the crayfish hemocyte cDNA. The primer sequences were: 871ϩ, 5Ј-TAATACGACTCACTA TAGGGAAGCTCACCGCTAACAACTCCG-3Ј and 1563Ϫ, 5Ј-TAATACGACTCACTATAGGGTGACTTCGGCTTCCT-GTGCT-3Ј for proPO gene; 477ϩ, 5Ј-TAATACGACTCACT-ATAGGGTGCCAGTCAGACAGAGGAAACG-3Ј and 1026Ϫ, 5Ј-TAATACGACTCACTATAGGGTTCAGTGCAAGAAGC-GGAGC-3Ј for pacifastin gene inhibitory domain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we identified a novel 43-kDa protein as a negative regulatory component of phenoloxidase (PO)-induced melanin synthesis (11). Also, it was reported that Drosophila serpin 27A specifically inhibited the proPO activating enzyme and prevented the melanin synthesis induced by activated PO and that the proteinase inhibitor, pacifastin, efficiently inhibited the proPO activating enzyme in a crayfish (9,12,13). However, a novel molecule working as a specific competitive inhibitor of PGN-dependent melanization cascade has so far not been found.…”
Section: Include Lipopolysaccharide (Lps) Peptidoglycan (Pgn)mentioning
confidence: 99%
“…More recently, the same sequence motif was also identified in Pacifastin, a 155-kDa protein from the crayfish Pacifastacus leniusculus and composed of two domains with different activities. One of these domains contains nine repeats similar to the locust peptides and has a protease inhibitory activity (7).…”
mentioning
confidence: 99%